ANALISA USAHA LANSIA POTENSIAL BERDASARKAN PASSION NYA DI PENDAMPINGAN LANSIA BOJONEGORO - Muhammad Soberi (Jurnal Manajemen dan Penelitian Akuntansi (JUMPA), 2019)
The purpose of this study is to analyze elderly businesses based on their desires in the Bojonegoro Elderly Assistance. This type of research is a qualitative study using phenomenology. Future experience motivates the elderly to determine the business in their old age. Based on observations and interviews involving several elderly people who participated in the Elderly mentoring program implemented by STIKES Maboro in collaboration with BMT Amanah and Kspps Akas, obtained the type of business chosen by the elderly for gardening, farming and farming. Of the three gardening activities that have the potential and are of interest to the elderly who are informants in this study.